COGNITIVE AND PHYSICAL FUNCTION TRAJECTORIES ASSOCIATED WITH MORTALITY: RESULTS FROM THE HEALTH ABC STUDY. (11th November 2018) - Handing, E; Leng, I; Hayden, K; Rosano, C; Harris, T B; Kritchevsky, S B
Abstract: Maintaining cognitive function and physical function are central to living a long and purposeful life. With increasing age, older adults often experience cognitive decline and mobility impairments, which have previously been studied as independent entities even though they commonly occur together. Few longitudinal studies have examined "dual decline": the concomitant decline in physical and cognitive function and its association to mortality. Utilizing data from the Health ABC study, we examined four trajectories of decline and time to death over 10 years. Results found that physical function decline was significantly associated with a higher risk of mortality (HR=1.23, 95% CI: 1.01- 1.51, p=.045) compared to no decline controlling for age, gender, race, and site. Risk factors associated with trajectories of decline will be investigated. Future intervention studies targeting cognitive and physical decline may be able to preserve function in older adults and improve independence.